2017
DOI: 10.1002/aur.1886
|View full text |Cite
|
Sign up to set email alerts
|

Auditory brainstem response in infants and children with autism spectrum disorder: A meta‐analysis of wave V

Abstract: Infants with autism spectrum disorder (ASD) were recently found to have prolonged auditory brainstem response (ABR); however, at older ages, findings are contradictory. We compared ABR differences between participants with ASD and controls with respect to age using a meta‐analysis. Data sources included MEDLINE, EMBASE, Web of Science, Google Scholar, HOLLIS, and ScienceDirect from their inception to June 2016. The 25 studies that were included had a total of 1349 participants (727 participants with ASD and 62… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 68 publications
1
27
0
Order By: Relevance
“…Third, it is the spontaneous activity of the brainstem (discussed in the section “Neurocircuitry Maturation”) that is thought to attune the auditory system long before the first auditory stimulus is propagated (reviewed in Friauf and Lohmann, 1999 ). The disruption of this developmental program may result in atypical auditory function, a behavior exhibited by many individuals with ASD ( Rosenhall et al, 1999 ; Khalfa et al, 2004 ; Miron et al, 2018 ; Otto-Meyer et al, 2018 ) and associated with autism severity ( Brandwein et al, 2015 ; Donkers et al, 2015 ). Overall, the principal role of the brainstem in hierarchical brain development suggests this region may have a major impact on how the symptoms of ASD unfold.…”
Section: Brainstem Anatomy and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, it is the spontaneous activity of the brainstem (discussed in the section “Neurocircuitry Maturation”) that is thought to attune the auditory system long before the first auditory stimulus is propagated (reviewed in Friauf and Lohmann, 1999 ). The disruption of this developmental program may result in atypical auditory function, a behavior exhibited by many individuals with ASD ( Rosenhall et al, 1999 ; Khalfa et al, 2004 ; Miron et al, 2018 ; Otto-Meyer et al, 2018 ) and associated with autism severity ( Brandwein et al, 2015 ; Donkers et al, 2015 ). Overall, the principal role of the brainstem in hierarchical brain development suggests this region may have a major impact on how the symptoms of ASD unfold.…”
Section: Brainstem Anatomy and Developmentmentioning
confidence: 99%
“…According to a recent meta-analysis, an increased ABR latency in youth with ASD changes into a decreased ABR latency in adults, which is indicative of an unusually fast developmental trajectory of ABR in ASD ( Miron et al, 2018 ). The rapid progression of ABR with age ( Cohen et al, 2013 ; Miron et al, 2018 ) suggests that the neurobiology supporting ASD symptoms may be highly malleable during specific periods, opening a possibility for time-sensitive interventions. In the future, longitudinal studies investigating age-related specificity of brainstem-based behaviors in ASD may help identify vulnerable developmental stages when intervention would be able to re-wire emerging neurocircuitry.…”
Section: Human Evidence For Brainstem Contributions To Asdmentioning
confidence: 99%
“…The amplitude of wave I was larger than that of wave V in more children (2-6 years of age) with ASD than in the age-matched TD controls [Santos et al, 2017]. Miron and his colleagues performed a meta-analysis on the recent literature regarding age-related changes in the latencies of ABR waves and reported that wave V latency was significantly prolonged across studies in children with ASD and was correlated negatively with age in ASD patients [Miron, Beam, & Kohane, 2017]. Taken together, the previous findings on the latency and amplitude abnormalities in the click-ABR indicate aberrant brainstem processing of the click sound in ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Contradictory findings have also been observed in neurophysiological and event-related potential (ERP) studies of pitch processing in ASD. A recent meta-analysis of results using these techniques suggests that infants and children (but not adults) with ASD have impaired auditory brainstem response to sound (Miron et al 2018). There are mixed reports regarding cortical sound encoding (P1-N1-P2), with enhanced (Ferri et al 2003), normal (Čeponienė et al 2003), and impaired patterns (Roberts et al 2011;Whitehouse and Bishop 2008) all reported.…”
Section: Introductionmentioning
confidence: 99%